2020
DOI: 10.2147/ccide.s259158
|View full text |Cite
|
Sign up to set email alerts
|

<p>Standardized <em>Arrabidaea chica</em> Extract Shows Cytoprotective Effects in Zoledronic Acid-Treated Fibroblasts and Osteoblasts</p>

Abstract: Introduction: Osteonecrosis of the jaw is a condition associated with intraoral ulceration and bone necrosis induced by antiresorptive medications, such as zoledronic acid, a bisphosphonate. Previous data on Arrabidaea chica (H&B.) Verlot wound healing activity prompted the study reported herein on A. chica standardized hydro alcoholic extract in vitro cytoprotective activity data on epithelial and osteoblastic cells exposed to zoledronic acid (ZA). Methods: Primary human gingival fibroblasts and murine pre-os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
3
0
10
Order By: Relevance
“…Scheper et al [ 51 ] showed that oral tissues treated with ZA had elevated expression of genes involved in the intrinsic (TNF, TRAF, death domain) and extrinsic (BCL, IAP, Caspase) apoptotic pathways, potentially explaining the increased rate of apoptosis observed in multiple studies. Increased caspase-3 and 9 activity, in cells treated with ZA and PA, as well as increased ROS production in N-BP-treated cells likely induced apoptosis in these cells [ 40 , 51 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scheper et al [ 51 ] showed that oral tissues treated with ZA had elevated expression of genes involved in the intrinsic (TNF, TRAF, death domain) and extrinsic (BCL, IAP, Caspase) apoptotic pathways, potentially explaining the increased rate of apoptosis observed in multiple studies. Increased caspase-3 and 9 activity, in cells treated with ZA and PA, as well as increased ROS production in N-BP-treated cells likely induced apoptosis in these cells [ 40 , 51 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…New formulations of alendronate or zoledronate by encapsulation in liposomes or nanoparticles are being investigated to increase their effectiveness and reduce the doses used [34]. On the other hand, intravenous administration of zoledronate [35] and the combination of zoledronate with other drugs [36,37] are being tested in order to reduce its adverse effects. These studies can be inspiring for stimulating research on the treatment of other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Foram encontrados os compostos majoritários 6,7,3′,4′-tetrahydroxy-5-methoxyflavylium, 6,7,4′-trihydroxy-5-methoxyflavylium, e carajurin após análise por HPLCDAD que podem justificar a atividade do AchE. O conteúdo de carajurin no AchE representa 6.51%±0.07% do seu total (Wiziack Zago et al, 2020)…”
Section: Rendimento Do Ache E Caracterização Químicaunclassified
“…Na literatura, diversos efeitos biológicos e farmacológicos da A. chica foram relatados, tendo destaque o seu potencial antimicrobiano demonstrando ação antifúngica contra algumas espécies de Candida (Hofling et al, 2010, Mafioletiet et al, 2013, Wiziack Zago et al, 2020, eficácia quando utilizada na cicatrização de feridas, efeito anti-inflamatório e atividade antioxidante (Giordani et al, 2015, Jorge et al, 2008, Medeiros et al, 2011, Aro et al, 2012, Oliveira et al, 2009, sendo utilizada geralmente na forma de extrato hidroalcoólico (Santos et al, 2013) ou diclorometano (Hofling et al, 2010).…”
Section: Introductionunclassified